Soil pH and Solubility of Aluminum, Iron, and Phosphorus in Ultisols: the Roles of Humic Acid - Hairil Ifansyah (JOURNAL OF TROPICAL SOILS, 2013)
Soil reaction (pH), aluminum (Al), iron (Fe) and phosphorus (P) are the parameters which presences in soil are related to each other. The role of each parameter on the grow than development of plants is very significant. Liming and organic mater amendment are some efforts that are frequently performed to increase the pH and P solubility and suppress the solubility of Al and Fe in the soil. Humic acid is one of the organic fractions which is presumed has roles and is closely related to the changes in soil chemical properties as mentioned above. Information about the role of humic acid on the soil pH, the solubility of Al, Fe, and P, especially in upland acidic Ultisols is still limited.  This study aims to: provide empirical data on the roles of various humic acids to soil pH and the solubility of Al, Fe, and P, specifically in upland acidic Ultisols.  The study was a laboratory experiment with a single factor which set by using a completely randomized block design and conducted in two sets of experiments. The first experiment is intended to study the roles of various humic acids derived from several sources (commercial humic acid, humic acids extracted from composted chicken manure, humic acids extracted from composted cow manure and humic acids extracted from composted goat manure) to the soil pH and solubility of Al, Fe, and P. The second experiment was aimed to see the patterns of relationships between application of humic acid (sold commercially) on pH and solubility of Al, Fe, and P. The results showed that humic acid was able to increase the soil pH, solubility of phosphorus, and suppressed the solubility of iron and aluminum with linear patterns of relationships. In increasing the pH, solubility of phosphorus, and suppressing the solubility of iron and aluminum in the soil, humic acid that is sold commercially, at the same amount of C-organics, has greater roles than those derived from organic matter of compost extracts and from organic matter of compost.Key words: Aluminum, Humic acid, iron, pH, phosphorus[How to Cite: Ifansyah H. 2013. Soil pH and Solubility of Aluminum, Iron, and Phosphorus in Ultisols: the Roles of Humic Acid. JTrop Soils 18 (3): 203-208. Doi: 10.5400/jts.2013.18.3.203][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.203]REFERENCESAgbenin JO.  2003.  Extractable iron and alumunium effects on phosphate sorbtion  in a Savanna Alfisol.  Soil Sci Soc Am J 67: 589-595Andrian RDP. 1990.  Hubungan Antara Susunan Asam Humat dan Asam Fulfat serta Kemasaman Total Bahan Organik Tanah dengan pH Tanah. Aluminium dan N Tersedia. [Skripsi]. FakultasPertanian Universitas Lambung Mangkurat.  Banjarbaru.Antelo J, F Arce, M Avena,  S Fiol, R Lopez and F. Macias.  2007.  Adsorption of humic acid at the surface of goethite and its competitipe interaction with phosphate.  Geoderma 138: 12-17.Arifin F, B Radjagukguk and BH Purwanto.  2009.  Phosphate and ferrous solubility on acid sulphate soils treated with rice straw. J Trop Soils 14: 119-125Balai Penelitian Tanah. 2005.  Petunjuk Teknis Analisis Kimia Tanah. Tanaman Air. Dan Pupuk.  Balai Penelitian Tanah Badan Penelitian dan Pengembangan Pertanian Departemen Pertanian.  Bogor. (in Indonesian).Bohn HL, BL McNeal and GA O’Connor.  1985.  Soil Chemistry (second edition).  John Wiley  & Sons Inc.  New York. Chichester. Brisbane. Toronto. Singapore.  pp. 135-141.Gupta US.  1997.  Crop Improvement Volume 2: Stress Tolerance.  Science Publishers. Inc.  303 p.Hayes MHB and RS Swift.  1990.  Genesis, isolation. composition and structures of soil humic substances. In:  MF De Booth, MHB Hayes and A Herbilon (eds). Soil Colloids and their Associations in Aggregates. Plenum Press. New York. pp. 245-305.Kononova MM, T Z  Nowakowsky and ACD. Newman.  1986.  Soil Organic matter its Nature. its Role in Soil Formation and in Soil Fertility.  Permagmon Press.  Oxford.Leiwakabessy FM.  1989. Management of Acid Humic Tropical Soils in Indonesia. In: ET Craswell and E. Pushparajah (eds). Management of Acid Soils in the Humid Tropics of Asia. ACIAR  Monograph No.13 (IBSRAM Monograph No.1), pp. 54-61Minardi. 2006.  Peran Asam Humat dan Fulvat dari bahan Organik dalam Pelepasan P Terjerap pada Andisol. Ringkasan Disertasi (tidak dipublikasikan).  Program Pascasarjana Universitas Brawijaya.  Malang.  Prasetyo BH and DA Suriadikarta. 2006. Karakteristik. Potensi. dan Teknologi Pengelolaan Tanah Ultisol untuk Pengembangan Pertanian Lahan Kering di Indonesia. J Litb Pert 25: 39-46.Rima V.  2002.  Acidification of soil-the indicator of chemical soil degradation process.  World  Congress of Soil Science 17. 14-21 August 2002. Thailand.  Paper  No. 10: 1-7Stevenson FJ. 1994. Humus Chemistry: Genesis. composition. reactio. 2nded. John Wiley and Sons. Inc. New York. Subandi. 2007. Teknologi produksi dan strategi pengembangan kedelai pada lahan kering masam. Iptek Tanaman Pangan 12: 12-24.Suntoro. 2001. Pengaruh residu penggunaan bahan organik,  dolomit dan KCl pada tanaman kacang tanah (Arachis hypogeae,  L.)  pada  Oxic Dystrudept  di Jumapolo, Karanganyar. Habitat 12: 170-177.Tan KH.  1995.  Dasar-Dasar Kimia Tanah.  Gadjah Mada University Press.  pp. 37-53.Ulfin I. and D Setyowati.  2007.  Optimasi kondisi penyerapan ion aluminium oleh asam humat.  Akta Kimindo. 2: 88-90.USDA [United State Department of Agriculture].  1999.  Liming to Improve Soil Quality in Acid Soils.  Technical Note No. 8. May 1999.  Independence Avenue. SW. Washington. D.C.20250-9410Winarso S, E. Handayanto and A Taufik.  2010.  Alumunium detoxification by humic substance extracted from compost of organic wastes.  J Trop Soils 15: 19-24.  Yusran FH.  2008.  Existing versus added soil organic matter in relation to phosphorus availability on lateritic soils.  J Trop Soils 13: 23-34.